The Effect of a Mixture of Bioethanol with Octane 92 Fuel on Gasoline Engine Vibration - Yuniarto Agus Winoko; Hersanda Aditya Pangestu (Institut Teknologi Sepuluh Nopember, 2023)
Along with technological developments, the system in vehicle engines is also experiencing developments, with the technology embedded in vehicle engines it is hoped that vehicles can become more efficient, powerful, produce low emissions, even vibration and sound produced is very small. This also needs to be supported by using the right fuel. Bioethanol is an alternative fuel made from vegetable and can produce complete combustion. The data collection method is by recording the proportion of the bioethanol mixture with 92 octane fuel and changes in engine speed, when vibrations occur, the LCD vibration meter will display the vibration value. Engine speed starts from 1500 to 8500rpm with a change of 1000rpm each rotation. From the tests carried out, at engine speed of 1500 to 2500 rpm the 5% mixture is a good mixture because the vibration value is lower than before mixing. Then for engine speed of 3500 to 8500 rpm a 10% mixture is a good mixture because the vibration value is lower than before mixing and lower than other mixtures.